The problems of soy market development in the far east and the ways of their solutions - Alexander V Gorlov; Claudia S. Churilova; Valery V. Reimer (Institute of Advanced Engineering and Science, 2019)
Soybean production is the main branch of specialization of agriculture in the south of the Far East, which is due to the unique natural advantages associated with favorable climatic conditions for the cultivation of this crop. In Russia, soybean as an agricultural crop has not historically found wide distribution, which is due to the exacting nature of this plant for various factors of production, the undeveloped culture of consumption of soy products in the diet of the population. Therefore soybeans were more used as technical raw materials for the production of the most important products of its processing - oil and meal. The purpose of this study is to identify trends in the soybean seeds market in the Far East and develop recommendations for improving the efficiency of its functioning in modern conditions. The methodology of soybean market research is based on the synthesis of economic analysis and applied methods developed in mathematical statistics. The scientific value of the results of the study is to identify the development trend of the soybean market localized in the Far East of Russia and to develop practical recommendations that complement the main provisions of the theory of spatial development and institutional configuration of market structures in the agrarian sphere.